ENGLISH WORD FORMATION IN THE JAKARTA POST’S POLITICS ARTICLES - Defitri Herlambang; Dewi Nurmala (Fakultas Sastra UMN AL Washliyah, 2022)
This study aims to identify the types of word formation that appear in politics articles and then to find out the dominant type in the data. The process of word formation is one of the important things to analyze because without realizing it often occurs in our daily lives. This research uses qualitative research method. The data used in the form of political articles in the 2021 edition of The Jakarta Post is 10 articles. In this study, there are several types used by researcher to collect and analyze data, including reading articles, identifying words, classification based on types of word formation, describing data and finally making conclusions. The results of this study show that there are 10 types of word formation based on Yule’s theory. Researcher found 370 words from 7 types of word formation and 3 other types were not found, including compounding 31 words (8,37%), blending 1 word (0,27%), clipping 4 word (1,08%), back formation 4 words (1,08%), acronym 20 words (5,40%), multiple process 1 word (0,27%), affixation 309 words (83,51%). Coinage, borrowing, and conversion are not found in the data. Based on calculations, the researcher concluded that affixation is the dominant type of word formation that appears in The Jakarta Post’s political articles.